Learning Malaysian Musical Instrument through Interactive 2D Games - Masmuzidin, Masyarah Zulhaida; Ishak, Nurul Hidayah (Journal of Computing Technologies and Creative Content, 2021)
Malaysia is a multiracial country with a wealth of local musical heritage and musical instruments. Nowadays, traditional musical instrument is difficult to find. Young generation are more exposed to the game based on computers and digital platform. The aim of this research is to create a 2-dimensional (2D) interactive game application by using Unity software. This research use ADDIE model as its methodology which consists of Analysis, Design, Development, Implementation, and Evaluation phase. A study on the effectiveness of interactive 2D game application on traditional musical instruments showed that respondents agreed that this application can exposed students with traditional musical instruments.